Influence of Brand Awareness, Brand Image, and Key Opinion Leaders on Hanasui Product Purchase Decisions - Ardiyanti, Vika Diyah; Fitriani, Itsna Rahma (Politeknik Negeri Semarang, 2024)
The skincare business in Indonesia is growing very rapidly. In the midst of intense competition for skincare products, skincare manufacturers are competing to offer products that suit consumers' needs and desires with various innovations and advantages. Apart from that, manufacturers are also aggressively promoting their products on social media using various methods to build brand awareness and brand image, which are very important assets because they can influence consumer perceptions and behavior. But currently, there is chaos in the world of skincare in Indonesia. Moreover, it is related to allegations that the ingredients in the product do not necessarily correspond to those listed and reported to BPOM. This problem has gone very viral since the appearance of a doctor known as the